Chronic stress disrupts neural coherence between cortico-limbic structures - Oliveira, João F.; Dias, Nuno S.; Correia, Mariana; Gama-Pereira, Filipa; Sardinha, Vanessa M.; Lima, Ana; Oliveira, Ana F.; Jacinto, Luís R.; Ferreira, Daniela S.; Silva, Ana M.; Reis, Joana S.; Cerqueira, João J.; et al. (Frontiers in Neural Circuits, 2013)
Chronic stress impairs cognitive function, namely on tasks that rely on the integrity of cortico-limbic networks. To unravel the functional impact of progressive stress in cortico-limbic networks we measured neural activity and spectral coherences between the ventral hippocampus (vHIP) and the medial prefrontal cortex (mPFC) in rats subjected to short term (STS) and chronic unpredictable stress (CUS). CUS exposure consistently disrupted the spectral coherence between both areas for a wide range of frequencies, whereas STS exposure failed to trigger such effect. The chronic stress-induced coherence decrease correlated inversely with the vHIP power spectrum, but not with the mPFC power spectrum, which supports the view that hippocampal dysfunction is the primary event after stress exposure. Importantly, we additionally show that the variations in vHIP-to-mPFC coherence and power spectrum in the vHIP correlated with stress-induced behavioral deficits in a spatial reference memory task. Altogether, these findings result in an innovative readout to measure, and follow, the functional events that underlie the stress-induced reference memory impairments.